The non-financial benefits of developing local suppliers for a large South African company - Erasmus, Willem (My University, 2014)
This study demonstrated that a large South African company was able to obtain operational benefits from its supplier development programme aimed at its disadvantaged suppliers. This is despite the fact that these supplier development efforts appeared to be undertaken to further social responsibility business objectives rather than to secure competitive advantage through supply chain The study demonstrated that the process used to identify projects for these initiatives and the scope of supplier development programmes played a significant role in determining the outcomes of these initiatives. It was found that most of the assisted businesses were small suppliers of non-essential goods and services. The majority were referred either by business units within the company, or the procurement department for the purpose of addressing poor performance and non-compliance to the company’s safety and quality standards. The supplier development function provided a wide range of services, ranging from training programmes and assistance aimed at struggling businesses, to providing more substantial resources and funding to growing and expanding suppliers that provide important services to the company. A special effort was made to increase the long-term sustainability of the supplier businesses by providing additional measures such as essential management and skills training. Although the programme was not specifically aimed at businesses with high BEE scorecard recognition levels, a significant component of the supplier development effort went into gaining or improving the BEE recognition levels of the supplier businesses. A very interesting finding of this study is that these benefits were derived, even when the company did not appear to have a clear intention to derive operational benefits from their supplier development programmes. Gaining recognition for its BEE scorecard appeared to be a strong driver for these initiatives. In contrast, the personnel of the supplier development function appeared to provide the main drive for the operational benefits that were obtained. Several noted that the company should, and did to some extent, have consideration for deriving benefits from these initiatives. Furthermore, the view was expressed that the most beneficial approach is to align the supplier development strategy with both the company’s preferential procurement targets and its supply chain imperatives. A few exemplary projects were encountered where specific needs and opportunities for products/services that addressed essential operational issues were identified. Collaborative development between the company and the iv suppliers resulted in significant improvements in the quality and availability of these products. It is recommended that the supplier development function proactively identifies similar projects for suppliers that are closer to the operations of the company and where clear benefits for the company can be obtained. The significance of this study is that it demonstrates that supplier development initiatives for disadvantaged supplier businesses, which are sometimes perceived as corporate social responsibility imperatives or compliance to the BEE Act, can add value to the buying company. It further provides insight into aspects of the implementation of a supplier development programme and indicates improvement areas. It also encourages long-term sustainability of these projects in order to have a lasting effect on the socio-economic transformation of the South African economy. excellence. The most significant benefit derived from the supplier development programme was ensuring compliance from suppliers with company requirements, for example for quality or safety. In addition, the large firm achieved improvements in quality, cost and reliability of products and services. However, the study also found that there were significant unrealised opportunities that the company did not appear to reap, such as improvement in supplier flexibility, securing environmental benefits, and the delivery of innovation inputs. One of the recommendations of this study is, therefore, that the company should attempt to strengthen its efforts in these directions. A mixed-method case study approach was followed to investigate the supplier development programme of a typical large South African company. Primary (qualitative) information was collected through semi-structured interviews with a core group of individuals that were involved in the supplier development programmes of the company, selected external persons that were either involved or knowledgeable in the areas of supplier development and/or BEE, and owners of businesses that participated in the supplier development programme. Secondary (quantitative) data were obtained from internal documents from the supplier development function, which outline the nature and scope of each of the 102 projects that were undertaken. Four aspects were explored: 1) The selection of participating supplier businesses, 2) assistance provided to these businesses, 3) the operational benefits obtained from these projects, and 4) the intention of the company to obtain operational benefits from this programme.
MBA thesis
Keywords: Supplier development programme; Social responsibility